Effectiveness and Safety of Ombitasvir-Paritaprevir/Ritonavir and Dasabuvir With or Without Ribavirin for HCV Genotype 1 Infection for 12 Weeks Under Routine Clinical Practice. (November 2016) - Chamorro-de-Vega, Esther; Gimenez-Manzorro, Alvaro; Rodriguez-Gonzalez, Carmen Guadalupe; Escudero-Vilaplana, Vicente; Collado Borrell, Roberto; Ibañez-Garcia, Sara; Lallana Sainz, Elena; Lobato Matilla, Elena; Lorenzo-Pinto, Ana; Manrique-Rodriguez, Silvia; Fernandez-Llamazares, Cecilia M.; Marzal-Alfaro, MariaBelen; et al.
Background: No previous studies exist examining the effectiveness and safety in real clinical practice of the combination of ombitasvir/paritaprevir/ritonavir and dasabuvir (OBV/PTV/r+DSV).Objective: To evaluate the effectiveness and safety in real clinical practice of the combination of OBV/PTV/r+DSV with or without ribavirin for 12 weeks in treatment-naïve and previously treated adult patients with chronic hepatitis C virus (HCV) genotype 1 infection.Methods: This was an observational study of a prospective cohort of treatment-naïve and pretreated adult patients who received 12 weeks of OBV/PTV/r (25/150/100 mg once daily) and DSV (250 mg twice daily) with or without ribavirin. The primary effectiveness outcome was sustained virological response 12 weeks after the end of treatment (SVR12). Safety outcomes were presented by the incidence of adverse events.Results: A total of 116 of 121 patients achieved a SVR12 (95.9%, 95% CI = 90.6-98.6). The SVR12 rate was 93.8% (95% CI = 86.0-97.9) in cirrhotic patients and 100% (95% CI = 91.4-100.0) in noncirrhotic patients. Adverse events occurred in 91.7% of patients, of which 81.8% were grade 1/2, and none led to premature discontinuation. Grade 3 adverse events were reported in 9.9% of patients. The most frequent adverse event was anemia (52.1%), although only 1.6% had a hemoglobin level below 8 g/dL. The incidence of any adverse event was higher in the group of patients who received ribavirin (96.5% vs 80.0%, P = 0.002).Conclusions: The combination of OBV/PTV/r+DSV with or without ribavirin for 12-week settings achieved a high rate of SVR12, with an acceptable safety profile in routine clinical care.